De Novo Class of Momordicoside with Potent and Selective Tumor Cell Growth Inhibitory Activity as Pyruvate Kinase Muscle Isozyme 2 and Anti-apoptotic Myeloid Leukemia 1 Inhibitors - Tope Abraham Ibisanmi; ‪Jamiu Olaseni Aribisala; Peace Ifeoma Odjegba; Damilola Ademuyi; Ayomide Akinmusere; Faith I Ajayi (Journal of Molecular Docking, 2022)
The difficulty in treating cancer resides in targeting abnormal proliferation while protecting normal proliferation, necessitating a thorough comprehension of the normal and malignant mechanisms that promote cell growth and proliferation. Targeting cell death signaling pathways such as glycolytic and mitochondrial apoptosis is the hallmark of many cancers, the aim of which this research is ready to evaluate. Atomistic molecular dynamics simulation of top hits after molecular docking and ADMET profiling of the ligands were performed for main protease-hit complexes. Docking scores of ligands used against PKM2 range from –9.36 to –12.1 kcal/mol, wherein momordicoside-F2 had the highest score (2.1 kcal/mol), performing better than the FDA-approved drug benserazide. Likewise, the scores ranged between –8.51 and –12.05 kcal/mol for Anti-apoptotic Myeloid Leukemia 1 (MCL-1), with momordicoside-F1 being the highest-ranked compound. The RMSD plots depicted stable trajectories with consistent and minor fluctuations implying that the protein (PKM2 and MCL1) backbone underwent minor structural perturbations. In addition, several significant peaks of increased fluctuations were also observed, indicating their increased interaction potential, implying that the ligands could adapt well in the protein's binding pocket. The SASA analysis results show that the ligands retained inside their shallow binding pocket. The phylogenetic tree obtained implies the likelihood of recurring results of the in silico profiling. Conclusively, this research unveils that Mormordicoside F1 shows good stability with MCL-1, likewise, momordicoside-F2 against PKM2. These hits can be a better re-purposing option.